Pendekatan Pendidikan Atau Dakwah Para Wali di Pulau Jawa - Rubini Rubini (Jurnal Al-Manar, 2015)
Walisongo is the name of a council or board of missionary propaganda. If there is one parent is away or died then it will soon be replaced by another guardian. Walisongo era is the era of the end of the dominance of the Hindu - Buddhist cultural heritage to be replaced with Islamic culture. They are a symbol of the spread of Islam in Indonesia. Particularly in Java. Of course many other figures who also play a role. But they are very big role in establishing the Islamic kingdom in Java, also its influence on the culture of the community at large as well as direct propaganda, making "nine trustees" is more widely known than others. The success of the saints in the spread of Islam can not be separated from an educational approach or method that is very important and we need to learn, that this approach does not leave all the cultures that existed previously.